Visual Observation and Metacognitive Regulation Errors in Geometry Problem: An Analysis of Secondary Students’ Thinking - Ainu Putri Rahmawati,; Sri Suryanti,; Anugrah Tegar Putra Farabibah, (Media Pendidikan Matematika, 2025)
This study analyzes secondary students’ errors in visual observation and metacognitive regulation while solving geometry problems involving triangles and quadrilaterals. Using a descriptive qualitative approach, three students representing high, moderate, and low mathematical ability levels demonstrated distinct error types. Students with high mathematical ability showed accurate visual observation and effective planning and monitoring but frequently neglected the evaluation stage. Students with moderate ability missed several visual cues and made errors in monitoring and evaluating their solutions. Those with low ability struggled across all indicators, showing minimal visual observation and multiple metacognitive regulation errors. Although all students performed basic visual observation, none carried out deep and critical evaluation. This study is limited by the small sample size, which restricts generalizability. Future research should involve larger and more diverse participants and examine instructional interventions designed to strengthen students’ visual observation and metacognitive regulation skills in geometry learning.